The Culture and Traditions of Karo Society as Part of Indonesian Cultural Heritage - Piter Sembiring; Marsel Ridky Maulana (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
This study examines the customs and traditions of Karo society as an integral part of Indonesian cultural heritage by positioning them as an interconnected cultural system. Using a literature-based research approach, this study reviews scholarly works addressing kinship systems, customary rituals, cultural expressions, traditional arts, and ethnoculinary practices within Karo society. Data were analyzed through critical reading and conceptual synthesis to identify key thematic patterns. The findings indicate that Karo customs function not as isolated practices but as a cohesive social system in which kinship, life-cycle rituals, artistic expressions, and traditional cuisine collectively shape social order and cultural identity. Moreover, Karo traditions demonstrate adaptability to social change while maintaining core customary values. This study highlights the importance of situating Karo customs within the broader context of Indonesian culture, emphasizing their role in the dynamic landscape of the Indonesian archipelago’s cultural diversity